2014
DOI: 10.1016/j.compmedimag.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of near-term risk of developing breast cancer using computerized features from bilateral mammograms

Abstract: Asymmetry of bilateral mammographic tissue density and patterns is a potentially strong indicator of having or developing breast abnormalities or early cancers. The purpose of this study is to design and test the Global asymmetry features from bilateral mammograms to predict the near-term risk of women developing detectable high risk breast lesions or cancer in the next sequential screening mammography examination. The image dataset includes mammograms acquired from 90 women who underwent routine screening exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 41 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…Experiment 1 asked if the abnormality signal was based on a disruption in the usual bilateral symmetry of the breasts. Studies have noted that asymmetry can be a strong indicator for developing breast cancer (27,28). Indeed, research has suggested that bilateral mammographic density asymmetry could be a significantly stronger risk factor for breast cancer development in the near-term than either woman's age or mean mammographic density (29).…”
mentioning
confidence: 99%
“…Experiment 1 asked if the abnormality signal was based on a disruption in the usual bilateral symmetry of the breasts. Studies have noted that asymmetry can be a strong indicator for developing breast cancer (27,28). Indeed, research has suggested that bilateral mammographic density asymmetry could be a significantly stronger risk factor for breast cancer development in the near-term than either woman's age or mean mammographic density (29).…”
mentioning
confidence: 99%
“…The study results demonstrated a statistically significant (positive) associations (with AUC = 0.767 ± 0.019) between the modelgenerated risk prediction scores and the actual near-term risk of a woman having an image-detectable breast abnormality that may lead to the development of breast cancer in the next subsequent examination. This study is also different from the previously reported near-term risk prediction studies 23,25 that used the image features directly computed from the original image of the whole breast area. In this study, we tested and implemented a new multiscaled feature analysis method and systematically investigated the correlations of a large number of texture features on the multiscaled regions with the risk of cancer development.…”
Section: Discussionmentioning
confidence: 74%
“…The details of these algorithms can be found in our previous publications. 23,31,32 Once the breast region was identified, we performed a kclass fuzzy c means (FCM) clustering to partite it into several subregions and each one has relatively homogeneous density values. Instead of stratifying breast areas into dense and fatty regions only, 30,[33][34][35] more subregions were extracted and analyzed from the original breast depicted on mammogram.…”
Section: B Mammographic Subregions Segmentationmentioning
confidence: 99%
See 2 more Smart Citations